Eric was rock climbing. At one point, he stopped and climbed straight down


\[2\dfrac{1}{2}\] meters. Then he climbed straight up

\[6\dfrac{3}{4}\] meters. Eric was wondering what his change in elevation was after these two moves.
Which of the following equations matches the situation above?
Choose 1 answer:
Choose 1 answer:
(Choice A)


\[-2\dfrac{1}{2} - 6\dfrac{3}{4} = \:?\]
A


\[-2\dfrac{1}{2} - 6\dfrac{3}{4} = \:?\]
(Choice B, Checked)


\[2\dfrac{1}{2} - 6\dfrac{3}{4} = \:?\]
B


\[2\dfrac{1}{2} - 6\dfrac{3}{4} = \:?\]
(Choice C)


\[-2\dfrac{1}{2} + 6\dfrac{3}{4} = \:?\]
C


\[-2\dfrac{1}{2} + 6\dfrac{3}{4} = \:?\]

3 answers

Since Eric climbed straight down 2 and 1/2 meters and then climbed straight up 6 and 3/4 meters, his change in elevation is the difference between the two distances. Thus, the equation that matches the situation is:

\[2\dfrac{1}{2} - 6\dfrac{3}{4} = ?\]

The correct answer is (Choice B).
the correct answer was C
I apologize for the confusion. You are correct, the correct answer is (Choice C):

\[-2\dfrac{1}{2} + 6\dfrac{3}{4} = ?\]